Molecular-Level Chemical Characterization of Dissolved Organic Matter in the Ice Shelf Systems of King George Island, Antarctica - Jang, Jiyi; Park, Jiyeon; Ahn, Seohee; Park, Ki-Tae; Ha, Sun-Yong; Park, Jongkwan; Cho, Kyung Hwa (Frontiers in Marine Science, 2020)
Antarctic shelf systems play an important role in organic matter circulation on Earth; hence, identifying the characteristics of dissolved organic matter (DOM) can be a good indicator for understanding its origin, as well as climate change. In this study, to identify the characteristics of DOM in the ice shelf systems, surface water was collected from the open sea (OS) and Marian cove (Fjord; FJ). Although there were no differences in DOM characteristics between sampling sites in quantitative analyses, the DOM in surface water of each region seemed to be more affected by terrestrial than marine biological sources in optical and molecular properties. This finding indicates that the terrestrial DOM related to mosses based on the molecular properties results; high levels of lipid-like (35–39%) and unsaturated hydrocarbon-like (UH; 27–34%) in both the OS and FJ regions, and significantly higher tannin-like substance and condensed aromatic structures (CAS) in the FJ than the OS region. When comparing the FJ transect samples, those nearest to a glacier (FJ1; 0.93 km from the glacier) showed relatively low salinity, high dissolved organic carbon (DOC), and high chromophoric DOM (CDOM), indicating that terrestrial DOM (possibly produced by moss) inflow occurred with the runoff from the freshly melting land ice and glacier. However, no significant differences in molecular composition were detected, suggesting that terrestrial DOM introduced into the ice shelf systems by melting land ice and glacier runoff could be a major source of DOM-rich seawater during austral fall, when low marine biological activity occurs. This study has a great significance as background data for DOM characteristics in the ice shelf systems due to the enhanced biological activity during the austral summer.